A multiscale experimental approach for correlating global and local deformation response in woven composites. (15th June 2018) - Koohbor, Behrad; Ravindran, Suraj; Kidane, Addis
Abstract: A multiscale experimental approach is introduced that facilitates correlating globally applied stress to the local material response at yarn scale. Using a high-resolution optical digital image correlation, low and high strain zones in off-axis woven composite samples loaded in uniaxial tension are identified and the corresponding full-field strains are quantified. The local strain response quantified over low and high strain domains are used along with the continuum scale deformation to establish a correlation between global and local deformation behavior as a function of fiber orientation. In addition, global stress-local strain curves are extracted for low and high strain domains at different fiber orientation angles. A simple plasticity model in conjunction with the obtained stress-strain curves is implemented and utilized to develop a phenomenological model that enables correlating global stress with the locally developed strain at different locations in a composite specimen subjected to off-axis tensile load.